2010
DOI: 10.1136/adc.2009.172395
|View full text |Cite
|
Sign up to set email alerts
|

What do research ethics committees say about applications to conduct research involving children?

Abstract: ObjectiveTo identify issues raised by Research Ethics Committees (RECs) in letters about applications to conduct research involving children. MethodsAnalysis of 80 provisional and unfavourable opinion decision letters written by RECs in response to applications to conduct research involving child participants. ResultsRECs were most likely to be concerned about issues relating to consent, recruitment, care and protection of participants, scientific design, and confidentiality. RECs focused on children's status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 5 publications
2
26
0
Order By: Relevance
“…Eight studies reported differences in the approach to consent, similar to our experience with the BBOP study (7). In particular, with juvenile subjects, research ethics committees focused on the children's status as vulnerable and expressed concerns about consenting procedures as well as emphasizing the need for children to be protected in research (8). The documented variability in these studies, as well as our experience with the BBOP study, represents an important burden to investigator-initiated multicentre studies, particularly those administered on limited budgets.…”
Section: Other Experiencesmentioning
confidence: 93%
“…Eight studies reported differences in the approach to consent, similar to our experience with the BBOP study (7). In particular, with juvenile subjects, research ethics committees focused on the children's status as vulnerable and expressed concerns about consenting procedures as well as emphasizing the need for children to be protected in research (8). The documented variability in these studies, as well as our experience with the BBOP study, represents an important burden to investigator-initiated multicentre studies, particularly those administered on limited budgets.…”
Section: Other Experiencesmentioning
confidence: 93%
“…Historically, ethics research committees have been viewed as the cautious gatekeepers,26 focused on children’s status as ‘vulnerable’. This is not often the case anymore, with regulators promoting a balanced approach, and valuing children’s researchers becoming engaged with developing regulation.…”
Section: How Then To Move Forward?mentioning
confidence: 99%
“…However, even though research ethics committees often express concerns about protecting children they see as specially ‘vulnerable’ (Angell et al . 2010), little is known about the psychological effect that taking part in research trials generally has on children and their families/parents, nor on the specific effects of participating in genetic trials.…”
Section: Introductionmentioning
confidence: 99%